Connecting in Isolation: Utilizing Community Circles to Build Relationships in Online Learning - Lomax, Danna; Lopez, Shannon; Veldman, Brittnee; Pereira, Monica (Allies for Education, 2020)
Many educators are currently teaching online due to the COVID-19 global pandemic. In distance learning, it can be a challenge for studnets and educators to create community. Community circles is a versatile practice that can be utilized to build relationships in both face-to-face and online environments. This paper offers a brief introduction to the practice of circles, discusses the preparation necessary to implement circles, and outlines the procedures for utilizing circles to foster classroom community.